THE ANALYSIS OF PORTER'S FIVE FORCES IN LUCKY TEXTILE GROUP IN FACING THE COMPETITION OF TEXTILE INDUSTRY - Kumbara, Afthon (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Lucky Textile Group is one of the textile industries in Indonesia. Lucky Textile Group has 2 subsidiaries, each of which has different processes and production results while maintaining mutual sustainability, namely PT. Benang Citra Indonesia and PT. Eternal Lucky Print. PT. Yarn Citra Indonesia is an industry that produces yarn with the main raw materials, namely cotton, rayon, capital, tencel and cotton blends, while PT. Lucky Print Abadi is an industry that produces woven and finishing fabrics (Printing, Dyeing and White). The raw material for making woven fabric is yarn obtained from PT. Yarn Citra Indonesia or can also be from an outside factory according to the appropriate type of raw material. Then processed into finishing fabrics (Printing, Dyeing and White) according to customer requests including special finishing such as waterproof, anti-fire, anti-bacterial etc. Market competition in Indonesia Even the world is getting stronger with the entry of new competition so this creates challenges that must be resolved. Improving efficiency, innovation and quality in the production process is a way to attract the attention of customers and do not forget to maintain customer confidence by implementing customer responses that encourage and meet customer demand Through the analysis of 5 porter strengths and SWOT analysis, it is expected that Lucky Textile Group can prepare and build strength in the current and future competition in the textile industry